Personel kancelaryjny Komitetu Wojewódzkiego PPR/PZPR w Lublinie w latach 1944–1956 - Czarnota, Tomasz (Komunizm: System - Ludzie - Dokumentacja, 2023)
From 1944 to 1956, the organisational model of the Provincial Committee (PC) of the Polish Workers’ Party’s (PWP)/Polish United Workers’ Party’s (PUWP) secretariat evolved from a centralised and consolidated to a decentralised and dispersed. In each of these two developmental stages, the personnel was slightly different both in terms of posts and the number of employees. Representatives of this group of the party apparatus were (PC PWP) the head of the General Secretariat, a secretary and a typist, and (PC PUWP) the secretariat’s clerks in the departments or the Secretariat of the First Secretary of the PC, a typist and a registrar. The number of PC PWP/PUWP administrative employees working in the secretariat in particular periods ranged from 3 (1944) to 27 people (1955). There were people with professional experience from various organisations (including district committees) and institutions, most of which can be described as the pillars of the “people’s power” [Security Office, Milicja Obywatelska, general administrative offices, youth organisations, such as the Union of Youth Struggle (ZWM) and the Union of Polish Youth (ZMP)]. The administration of the PC PUWP secretariat in Lublin almost entirely consisted of employees “inherited” from the Provincial Committee of the Polish Workers’ Party, not from the Provincial Committee of the Polish Socialist Party in Lublin. When compared to the political functionaries, the administrative employees were considered insignificant in the party’s full-time apparatus, as expressed, e.g., by their low earnings. They also had little promotion opportunities within this apparatus, which was one of the reasons for staff turnover. On the other hand, some people held administrative positions for four years (PC PWP), or even five and six years (PC PUWP). The administrative employees were rarely politically trained because they were not considered a source for future mid-level or senior-level political staff. Most of them were relatively young and poorly educated (usually primary education), with a party background that usually did not extend the legal existence of the PWP. In the times of the Central Committee of the Polish Workers’ Party, the employees were predominantly female, amounting to over 80 per cent. In the years of the PC PUWP, the secretariat was 100 per cent feminised.